A Novel mcr-1 Variant Carried by an IncI2-Type Plasmid Identified From a Multidrug Resistant Enterotoxigenic Escherichia coli - Liu, Hongbo; Zhu, Binghua; Liang, Beibei; Xu, Xuebin; Qiu, Shaofu; Jia, Leili; Li, Peng; Yang, Lang; Li, Yongrui; Xiang, Ying; Xie, Jing; Wang, Ligui; et al. (Frontiers in Microbiology, 2018)
In this study, we discovered a novel mobilized colistin resistance (mcr-1) gene variant, named mcr-1.9, which was identified in a colistin-resistant enterotoxigenic Escherichia coli (ETEC) strain from a clinical diarrhea case. The mcr-1.9 gene differs from mcr-1 at position 1036 due to a single nucleotide polymorphism (G→A), which results in an aspartic acid residue being replaced by an asparagine residue (Asp346→Asn) in the MCR-1 protein sequence. Antimicrobial susceptibility testing showed that the mcr-1.9-harboring ETEC strain is resistant to colistin at a minimum inhibitory concentration of 4 μg/ml. Plasmid profiling and conjugation experiments also suggest that the mcr-1.9 variant can be successfully transferred into the E. coli strain J53, indicating that the gene is located on a transferable plasmid. Bioinformatics analysis of data obtained from genome sequencing indicates that the mcr-1.9 gene is located on a 64,005 bp plasmid which has been named pEC26. This plasmid was found to have high similarity to the mcr-1-bearing IncI2-type plasmids pWF-5-19C (99% identity and 99% coverage) and pmcr1-IncI2 (99% identity and 98% coverage). The mcr-1.9-harboring ETEC also shows multidrug resistance to 9 classes of antibiotics, and contains several virulence and antimicrobial-resistance genes suggested by the genome sequence analysis. Our report is the first to identify a new mcr-1 variant in an ETEC isolated from a human fecal sample, raising concerns about the existence of more such variants in human intestinal flora. Therefore, we believe that an undertaking to identify new mcr-1 variants in the bacterial communities of human intestines is of utmost importance, and that measures need to be taken to control the spread of mcr-1 and its variants in human intestinal microflora.